La consulta previa como símbolo dominante: significados contradictorios en los derechos de los pueblos indígenas en México. Issue 2 (2nd April 2020) - Llanes Salazar, Rodrigo
ABSTRACT: In this article I analyze the right to free, prior and informed consultation (CPLI) as a dominant symbol to explore key contradictions in the field of indigenous rights in Mexico. According to the anthropologist Victor Turner, dominant symbols condensate disparate and even contradictory meanings. From this perspective, I address how the right to CPLI in Mexico has become a dominant symbol not only because of its remarkable presence in the demands of the country's indigenous organizations and activists, but also because it condensates contradictory meanings originated in social processes that range from neoliberal governance to indigenous struggles for self-determination and territory. As a result of these disparate processes, the right to CPLI not only has different meanings, but it is also mobilized by different actors for very different ends, in a struggle to fix the meaning of that right.